Letters from Frank Gallagher to Éamon De Valera regarding the "External Relations Act" and "Costello's conference", - Gallagher, Frank, 1893-1962 (1938)
Includes a letter from Harry S. Truman regarding the "External Relations Act", a letter regarding the dismissal of a "Maureen Kennedy" from the "Irish Press", a list of documents and books and a letter advising De Valera to be "very careful about Costello's conference".